(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
In November 2019, the African Court on Human and Peoples’ Rights in Rajabu v Tanzania issued its first major decision related to the substance of the death penalty. The Court found that Tanzania’s mandatory death penalty violated article 4 of the African Charter on Human and Peoples’ Rights (the right to life), because it constituted an ‘arbitrary’ deprivation of life. This decision accords with case law from other international treaty bodies and judgments of domestic courts. In addition, the Court found that hanging as a method of execution was ‘inherently degrading,’ a notable finding because most retentionist African countries still use hanging. By assessing the mandatory death penalty under article 4 instead of article 7 (right to a fair trial), the Court’s holding has limited applicability to other mandatory sentences, but the author contends that the Court should extend this precedent in the future to mandatory life imprisonment. The most important question that remains open is whether article 4 requires an individualised sentencing hearing in every case, including where persons with mandatory death sentences have already had their sentences commuted to imprisonment terms by the president without an opportunity to present mitigating evidence. Rajabu significantly contributes to the erosion of the death penalty in Africa and is an incremental precursor to total abolition under article 4 of the Charter.